Survival rates and causes of death in Tengmalm’s owl offspring during the post-fledging dependence period in Central and North Europe - Kouba, Marek; Bartoš, Luděk; Tulis, Filip; Stehlíková Sovadinová, Simona; Korpimäki, Erkki (Frontiers in Ecology and Evolution, 2024)
Offspring survival rates in altricial birds during the post-fledging period are an essential factor in determining the fitness of parents and have a significant impact on general population dynamics. However, our current knowledge of post-fledging mortality and its causes remains fragmentary in most bird species, and even less information is available on the mortality of individuals of the same species in different environments. In order to address this gap in our knowledge, we studied fledgling mortality and its causes in Tengmalm’s owls (Aegolius funereus) during six breeding seasons in Central and North Europe using radio-telemetry. A total of 80 nestlings from 18 nests in Czechia (2010–2012, 2015) and 60 nestlings from 24 nests in Finland (2019, 2021) were radio-tracked during the post-fledging dependence period. The overall survival rate was much higher in Czechia (83%) than in Finland (53%), with predation identified as the primary cause of mortality in both areas. Avian predation was far higher in Finland, but mammalian predation was equivalent at both study sites. Pine martens (Martes martes) and goshawks (Accipiter gentilis) were the most common predators in Czechia and Finland, respectively. Starvation and disease, or mostly a combination of both, formed the second most common cause of death in both areas but were much more frequent in Finland than in Czechia. Offspring survival in both study sites was considerably higher in years of food abundance than in those of food scarcity. We suggest that the interactive effects of infections and poor body condition due to scarcity of main prey species induced higher mortality rates in offspring, particularly in the more challenging environment of North Europe. In contrast, fledgling owls were found to be able to fight off infections more successfully during rich food seasons. Finally, we encourage researchers to pay greater attention to the mutual influences of parasites and their definitive hosts and stress the importance of using radio or satellite tracking for mortality studies to identify causes of death more accurately.